Application of a cross-functional approach to optimize the activities of a specialized vehicle depot - Elena A. Kaliberda; Ksenia V. Chemerilova; Olga G. Sheveleva (International Journal of Advanced Studies)
Background. The article considers the possibility of using cross-functional approach to analyze and optimize motor transport enterprise’s business processes. Cross-functional and end-to-end processes are basic approaches to process-based enterprise management. The article analyzes the peculiarities of application of each of the approaches, and also provides the justification of the necessity to create a cross-functional team to optimize the processes under consideration.